2009
DOI: 10.1029/2008ja013957
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity dependence of the topside ionosphere at low latitudes

Abstract: [1] We investigated the solar activity dependence of the topside ionosphere with ROCSAT-1 observations. The distribution of the plasma density at 600 km altitude shows features with considerable local time, season, and solar activity differences. In the daytime, plasma density peaks around the dip equator. This peak is more distinct in equinoxes and weaker in May-July, and it enhances with solar activity in all seasons. The seasonal behavior of this peak is primarily controlled by the seasonal variations of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…The increased atomic composition may affect NmF2 via dynamic processes even [O]/[N 2 ] is invariant between ME and SE. Chen et al (2009) indicated that the increased neutral density (without [O]/[N 2 ] changing) results in higher electron density at low latitudes. Thus the equinoctial difference of neutral density also affects the equinoctial asymmetry of the electron density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased atomic composition may affect NmF2 via dynamic processes even [O]/[N 2 ] is invariant between ME and SE. Chen et al (2009) indicated that the increased neutral density (without [O]/[N 2 ] changing) results in higher electron density at low latitudes. Thus the equinoctial difference of neutral density also affects the equinoctial asymmetry of the electron density.…”
Section: Discussionmentioning
confidence: 99%
“…Solar zenith is equal at March equinox (ME) and September equinox (SE), but the ionosphere presents some differences between the two equinoxes under equivalent solar activity conditions (e.g. Bailey et al, 2000;Balan et al, 1997Balan et al, , 1998Chen et al, 2009;Essex, 1977;Kawamura et al, 2002), namely ionospheric equinoctial asymmetry. This asymmetry may originate from the equinoctial differences in neutral winds, thermospheric composition and density, electric fields, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Many works showed the nonlinearity appearing in the variations of the ionospheric electron density with solar indices [e.g., Balan et al, 1994aBalan et al, , 1996Belehaki et al, 2001;Chen et al, 2008Chen et al, , 2009Gupta and Singh, 2000;Kouris et al, 1998;Liu et al, 2003Liu et al, , 2004aLiu et al, , 2006Liu et al, , 2007Liu and Chen, 2009;Ma et al, 2009;Park et al, 2008;Richards, 2001;Sethi et al, 2002;Su et al, 1999]. An important nonlinear character is the saturation effect that was found in the variations of N m F 2 (maximum electron density of the F 2 layer) or TEC (total electron content) with solar indices; namely, N m F 2 (TEC) increases linearly with solar indices with a higher rate at lower solar activity levels, whereas the increase rate decreases, or even N m F 2 (TEC) does not obviously increase, at higher solar activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Under the normal solar cycle condition, TEC peaks at the dip equator during equinoxes and at a low-latitude band of the summer hemisphere during solstices. At nighttime, with the vanishing of the equatorial fountain effect, the EIA structure disappears except at solar maxima when the pre-reversal enhancement of the upward plasma drift induces a strong EIA at sunset, which can last to nighttime (e.g., Chen et al 2009). There is no EIA structure after sunset at lower solar activity levels as the pre-reversal enhancement of the upward plasma drift is positively correlated with the solar activity level (e.g., Fejer et al 1991).…”
Section: Methods Of Extrapolating Else Tecmentioning
confidence: 99%